EXPERIMENTAL AND CFD ANALYSIS OF A LABORATORY-SCALE PARALLEL FLOW SHELL AND TUBE HEAT EXCHANGER - Alviani Hesthi Permata Ningtyas; Siti Duratun Nasiqiati Rosady; Ilham Arifin Pahlawan; Rilo Chandra Muhamadin (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
A heat exchanger is a device that functions to change the temperature of a fluid by utilizing the heat transfer mechanism from a high-temperature fluid to a lower-temperature fluid. This study was conducted to design and analyze the performance of a shell and tube heat exchanger with a parallel flow configuration on a laboratory scale. The design process focused on determining the main dimensions and components, such as tube length and the ratio between shell and tube diameters, to ensure optimal operation for laboratory experiments. After the device was successfully fabricated, experiments were carried out to obtain temperature data of the hot and cold fluids at both the inlet and outlet. These experimental data were then compared with the results of numerical simulations using ANSYS Fluent software based on the Computational Fluid Dynamics (CFD) method. The simulation was used to visualize the flow pattern and temperature distribution within the heat exchanger, as well as to calculate heat transfer efficiency. The results showed good agreement between the simulation and experimental data, with only a 1% deviation, where the inlet temperature of the hot fluid was 65°C and the outlet temperature was 38°C, indicating the validity of the numerical model used. From this study, it can be concluded that the combination of experimental design and CFD simulation analysis provides a more comprehensive understanding of the temperature distribution and efficiency of a shell and tube heat exchanger with a parallel flow configuration.